Notes on Early Land Plants Today. 39. Microlejeunea indica (Marchantiophyta, Lejeuneaceae) - Wei, Yu-Mei; Zhu, Rui-Liang (Phytotaxa, 2013)
The systematic position of the pantropical genus Microlejeunea Stephani (1888: 61) has been debated. Grolle (1995) first defined the precise generic concept of Microlejeunea, which was also confirmed by molecular studies (Wilson et al. 2004; Dong et al. 2013). This concept has recently been followed by various authors (e.g., He & Zhu 2011; Lavocat & Schäfer-Verwimp 2011; Thouvenot et al. 2011; Marline et al. 2012; Thiers et al. 2012). Microlejeunea is well characterized and easily separated from Lejeunea Libert (1820: 372) by the presence of ocelli in the leaf lobe, transverse section of stem consisting of seven cortical cells and three medullary cells, and keel of female bract usually winged (Wei & Zhu 2013). Lejeunea indica Udar & Awasthi (1981: 345), known only from India (Udar & Awasthi 1981; Joshi 1995; Zhu & Long 2003; Dey et al. 2008), has all essential characters of Microlejeunea. Thus, a new combination is needed.